Oral microbiota in cesarean-delivered puppies - Burgio, Matteo; Pellegrini, Francesco; Frattina, Lorenza; Carbonari, Alice; Bramante, Giovanni; Andriulo, Olga Maria; Camero, Michele; Lanave, Gianvito; Parisi, Antonio; Martella, Vito; Rizzo, Annalisa; Cicirelli, Vincenzo (Frontiers in Veterinary Science, 2025)
IntroductionThe microbiota plays a fundamental role in host health, and alterations in its composition have been associated with numerous pathological conditions. The neonatal period is a critical window for establishing a stable microbiota that shapes long-term health. The aim of this study was to characterize the oral microbiota of cesarean-delivered puppies at birth and 15 days postpartum, using 16S rRNA gene sequencing. This microbiota was compared with the maternal oral and colostrum microbiota.MethodsThe study included 15 puppies delivered by cesarean section from four French Bulldogs. Oral swabs were collected from puppies at birth (T0) and day 15 (T15), and from dams together with colostrum before anesthesia. DNA was extracted and the full-length 16S rRNA gene amplified with universal primers. Libraries were prepared, purified, and sequenced on a MinION Mk1C for 24 h. FastQ files were analyzed with EPI2ME (Fastq 16S), and taxonomic assignment was performed using the NCBI_16S database via BLAST.ResultsMicrobial DNA was detected in neonatal samples at birth, indicating that colonization had already begun. Diversity analyses showed significant differences between the puppies’ oral microbiota at T0 and T15 (p = 0.006), as well as between neonates at T0 and their mothers (p = 0.018). By contrast, no significant differences in alpha diversity were observed between puppies at T15 and their mothers, suggesting convergence toward an adult-like microbial profile. Colostrum did not show significant differences compared with the puppies’ oral microbiota at both time points, suggesting it may act as a possible, though not exclusive, source of microbial transfer.ConclusionThe oral microbiota of cesarean-delivered puppies undergoes rapid compositional changes within the first 15 days of life, marked by increased alpha diversity and a shift toward a microbial profile resembling that of the mother. Initial colonization likely derives from non-oral maternal or environmental sources, with convergence by day 15 due to maternal contact. Maternal colostrum did not significantly influence oral diversity, though it may act as a vector of microbial transfer. These findings underscore the dynamic nature of early-life colonization and contribute to our understanding of host–microbiota interactions in a One Health context.